The Pengaruh Kesadaran Hukum tentang Tujuan Perkawinan terhadap Perkara Perceraian Semasa Covid-19 (Kajian Hukum Menurut Fikih Munakahat dan Hukum Positif) - Thia Sasmita; Idaul Hasanah; Tinuk Dwi Cahyani (Universitas Muhammadiyah Malang, 2021)
The issue of divorce in the Malang Religious Court Class 1A (PA Malang) is still a worrying scourge. The dominating factor in the Annual Report of the Malang Religious Court 2020 is the ongoing dispute due to inadequate financial conditions. This research aims to identify legal awareness of the purpose of marriage in the community in PA Malang according to Fikih Munakahat and positive law, as well as its relevance to the case of divorce economic factors during Corona Virus Disease 2019 (Covid-19). This research is carried out through a juridical-empirical approach, in which norms in a rule are identified as being present in a particular community. The results of this study argue that the legal awareness of the purpose of marriage in the community in PA Malang during Covid-19 has not been implemented properly, so this is one of the factors of the large percentage of divorce cases economic factors on the pretext of continuous disputes. The influence of legal awareness of the purpose of public marriage in PA Malang on divorce cases during Covid-19 according to Fikih Munakahat and positive law has a great influence in establishing household integrity. Keywords: Legal awareness; Purpose of marriage; Divorce matters; Fikih Munakahat; Positive Law. Abstrak Masalah perceraian di Pengadilan Agama Malang Kelas 1A (PA Malang) masih menjadi momok yang mengkhawatirkan. Faktor yang mendominasi dalam Laporan Tahunan Pengadilan Agama Malang 2020 adalah perselisihan terus-menerus sebab kondisi finansial yang tidak memadai. Penelitian ini bertujuan untuk mengidentifikasi kesadaran hukum tujuan perkawinan pada masyarakat di PA Malang menurut Fikih Munakahat dan hukum positif, serta relevansinya dengan perkara perceraian faktor ekonomi semasa Corona Virus Disease 2019 (Covid-19). Penelitian ini dilaksanakan melalui pendekatan yuridis-empiris, yang mana norma dalam suatu aturan diidentifikasikan kehadirannya pada suatu komunitas tertentu. Hasil penelitian ini berpendapat bahwa kesadaran hukum tujuan perkawinan pada masyarakat di PA Malang semasa Covid-19 belum terimplementasi secara baik, sehingga hal inilah yang menjadi salah satu faktor besarnya persentase perkara perceraian faktor ekonomi pada dalih perselisihan terus-menerus. Pengaruh kesadaran hukum tujuan perkawinan masyarakat di PA Malang terhadap perkara perceraian semasa Covid-19 menurut Fikih Munakahat dan hukum positif memiliki pengaruh yang besar dalam menjalin keutuhan rumah tangga.